Resistant Hypertension: Questions and Contemporary Answers - V. I. Podzolkov; A. E. Bragina; K. K. Osadchiy (Рациональная фармакотерапия в кардиологии)
The review presents the important problem of resistant hypertension. Its real prevalence is unknown. According to population studies and metaanalyzes of clinical studies, the prevalence of this most severe form of hypertension reaches 12-15% in the general population and 15-18% in clinical cohorts. Over the past decades, an increase in its frequency among patients with hypertension has been noted. Based on the results of large-scale studies, risk factors are detected that allow to assess the risk for the resistance to antihypertensive drugs. Adherence to ongoing antihypertensive therapy is crucial to addressing the issue of hypertension resistance; there are acceptable ways to evaluate it in clinical practice. The review discusses the most common mistakes in the choice of therapy, which can cause resistance to antihypertensive treatment, namely irrational drug combinations, insufficient dosage of the drug, and the use of non-prolonged forms of drugs. The latest recommendations for the diagnosis and treatment of hypertension, including its resistant form, are analyzed. The review contains a rationale based on the results of randomized clinical trials, the choice antihypertensive strategy in this variant of arterial hypertension. The importance of fixed combination antihypertensive drugs, as well as thiazine-like diuretics and amlodipine is stressed. The results of studies demonstrate the rational for the use of antimineralcorticoid drugs, namely spironolactone, for this category of patients. The authors offer an updated algorithm for the diagnosis and treatment of resistant hypertension, based on the sections of the latest clinical recommendations on this problem.